2003
DOI: 10.1590/s0100-879x2003001100006
|View full text |Cite
|
Sign up to set email alerts
|

Production of a cloned calf from a fetal fibroblast cell line

Abstract: The present study examined the in vitro and in vivo development of bovine nuclear-transferred embryos. A bovine fetal fibroblast culture was established and used as nucleus donor. Slaughterhouse oocytes were matured in vitro for 18 h before enucleation. Enucleated oocytes were fused with fetal fibroblasts with an electric stimulus and treated with cytochalasin D and cycloheximide for 1 h followed by cycloheximide alone for 4 h. Reconstructed embryos were cultured for 7-9 days and those which developed to blast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…CCB and CCD have been widely used to prevent extrusion of pseudo PBs of G0/G1 somatic donors during the SCNT procedure [3]. With a similar purpose, exposure to these chemicals at different times, such as 1, 5 or 6 hr, have also been attempted in bovine [1,11,20,24,38]. In the present study, groups 1-4 showed extrusion rates ranging from 53-67%, whereas group 5 exhibited a significantly low rate of 22%.…”
Section: Discussionmentioning
confidence: 69%
“…CCB and CCD have been widely used to prevent extrusion of pseudo PBs of G0/G1 somatic donors during the SCNT procedure [3]. With a similar purpose, exposure to these chemicals at different times, such as 1, 5 or 6 hr, have also been attempted in bovine [1,11,20,24,38]. In the present study, groups 1-4 showed extrusion rates ranging from 53-67%, whereas group 5 exhibited a significantly low rate of 22%.…”
Section: Discussionmentioning
confidence: 69%
“…Samples were collected at a local slaughterhouse in Sao Paulo. Finally, bovine clones were produced by somatic cell NT according to the methods of Mello et al (2003), Yamazaki et al (2005) and Miglino et al (2007). For analyses, only specimens without clear signs of resorption or regression were used.…”
Section: Sample Collectionmentioning
confidence: 99%
“…On day 7 after fusion, embryo quality was evaluated and grades 1 and 2 blastocysts were transferred to recipients. For further details of the protocols, see Mello et al [22] and Yamazaki et al [23].…”
Section: Enucleation Nucleus Transfer and Culturementioning
confidence: 99%